Carboxymethyl chitosan/sodium alginate hydrogel films with good biocompatibility and reproducibility by in situ ultra-fast crosslinking for efficient preservation of strawberry - Zhang, Yuwei; Zhao, Wenxin; Lin, Zhenhao; Tang, Zhongfeng; Lin, Baofeng (Carbohydrate polymers, 2023)
Strawberry is a seasonal and regional fruit. Thus, strawberry waste caused by spoilage and decay is an urgent problem that must be solved. Developing hydrogel films (HGF) for multifunctional food packaging can effectively slow down strawberry. Based on the carboxymethyl chitosan/sodium alginate/citric acid with excellent biocompatibility, preservation effect, and ultrafast (10 s) coating on the strawberry surface, HGF specimens were designed and prepared through the electrostatic interaction of opposite charges between polysaccharides. The prepared HGF specimen exhibited excellent low moisture permeability and antibacterial properties. Its lethality rates against both Escherichia coli and Staphylococcus aureus were more than >99 %. The HGF could keep strawberries fresh for up to 8, 19, and 48 days at 25.0, 5.0, and 0 °C, respectively, by delaying the fruits' ripening, dehydration, microbial invasion, and respiration rate. The HGF dissolved and regenerated five times still exhibited good performance. The water vapor transmission rate of the regenerative HGF could reach 98 % of that of the original HGF. The regenerative HGF could maintain the freshness of strawberries for up to 8 days at 25.0 °C. This study provides new insight into an alternative film design for convenient, green, and renewable alternative films to delay perishable fruit spoilage.